Pengaruh Model Pembelajaran Problem Based Learning Berbasis Realistic Mathematics Education Terhadap Kemampuan Komunikasi Matematis Siswa ditinjau dari Kemandirian Belajar Siswa - Rahmayani Rahmayani; Nizlel Huda; Sugilar Sugilar (Universitas Batanghari Jambi, 2023)
This study aims to investigate whether there are differences in mathematical communication between students who follow the Problem Based Learning model based on Realistic Mathematics Education and students who follow the Direct Learning model based on independence with high, medium, and low categories of class XI students at SMA Negeri 5 Tebo. This study is a quasy-experimental study with a randomized factorial design. The sample of this study was selected by simple random sampling technique, with class XI IPS 1 as the experimental class and XI IPS 2 as the control class. The instrument used was a test used to measure students' mathematical communication skills and a questionnaire to measure student learning independence. The data analysis technique used in this study is a two-way ANOVA. Based on the results of data analysis, it can be concluded that: 1) There are differences in mathematical communication skills between students who study using the Problem Based Learning model based on Realistic Mathematics Education and students who learn using the Direct Learning model. 2) There are differences in mathematical communication skills between students who have high, medium, and low independence. 3) There is no interaction between the application of learning models (Problem Based Learning based on Realistic Mathematics Education in the experimental class and Direct Learning in the control class) and students' independent learning on students' mathematical communication skills.